Konsep Ketuhanan Animisme Dan Dinamisme: Animism, Dynamism - Rekka Wahyu (Jurnal Penelitian Multidisiplin, 2022)
The concept of divinity has been known since humans existed in the world. The basis of this concept of divinity is the existence of something supernatural. The earliest concepts of divinity were animism and dynamism. Both of these concepts began to exist since ancient human times and are very simple in nature. Everything that is supernatural is associated with the existence of God. Then, the concept of divinity develops along with the formation of the structure of society in humans. Thus, the question arises whether in this day and age there are still animists and dynamism beliefs. The purpose of making this journal is to increase knowledge about the concept of animism and dynamism. The method in making this journal is by collecting references from various books. The results of this journal can be seen that today there are still many tribes who adhere to animism and dynamism beliefs.